Effects of Incorporating Banana Skin Powder (BSP) and Palm Oil Fuel Ash (POFA) on mechanical properties of lightweight foamed concrete - Mohamad, Noridah; Abdul Samad, Abdul Aziz; Lakhiar, Muhammad Tahir; Othuman Mydin, Md Azree; Jusoh, Suriani; Sofia, A.; Efendi, Suaidi Azis (International Journal of Integrated Engineering, 2019)
This paper presents the effects of agricultural wastes on the mechanical properties of lightweight foamed concrete, LFC. The agricultural wastes utilized in this research are banana skin powder (BSP) and palm oil fuel ash (POFA) as cement and sand replacement, respectively. Physical and chemical tests were conducted to determine the chemical composition and particle size of both BSP and POFA. These chemical and physical properties of the raw materials are important in understanding the effects they have on the mechanical properties of lightweight foamed concrete incorporating BSP and POFA, which is designated as LFC-BSP-POFA. Cube, cylindrical, and prism specimens of LFC-BSP-POFA with density of 1800kg/m³ were cast and tested to determine its compressive strength, tensile strength, modulus of elasticity and flexural strength. Twelve (12) LFC-BSP-POFA mixtures were prepared with content of BSP as cement replacement of 0%, 0.2%, 0.4%, 0.6%, 0.8% and 1% by weight. For each mixture, the content of POFA as sand replacement are 0% and 15%. It was found that BSP and POFA each contain 55.98% and 51.83% silicon dioxide, and 2.71% and 2.32% aluminum oxide, respectively. The particle size for these two materials as obtained from PSA test showed that both materials are considered as fine particles, which is within 0.1µm to 250 µm. These chemical composition and particle size of BSP and POFA contribute to the pozzolanic reaction in LFC. This is proven by the results obtained from the mechanical properties tests which show that the incorporation of both BSP and POFA as cement and sand replacement have some significant effects on the mechanical properties of LFC. The increase percentage of BSP and POFA incorporated in LFC had shown slight increment in its mechanical properties.